2018
DOI: 10.1021/acs.bioconjchem.8b00708
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of Uptake of Tumor-Seeking Cyanine Dyes

Abstract: Molecular entities that localize in tumor tissue are clinically important for targeted delivery of diagnostic, imaging, and therapeutic reagents. Often these targeting entities are designed for specific receptors (e.g., EGFR or integrin receptors). However, there is a subset of cyanine-7 dyes that apparently localize in every type of solid tumor tissue (at least, no exceptions have been reported so far), and they persist there for several days. Consequently, these dyes can be used for near-IR optical imaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 71 publications
6
94
0
Order By: Relevance
“…[17] Conjugate 1 was designed to conform to several criteria. Second, the meso-chloro group of fluorophore A was not used to form conjugate 1.T he role of the meso-chloro functionality in the tumor-seeking properties of these dyes remainst ob ef ully elucidated, but we [21] and others [22] have shown that it is displaced by S-nucleophiles under physiological conditions, including the free cysteine residue in serum albumin.W eh ave also shown that the mesochloridec an be displaced to form ac ovalent albumin adduct that permeates into cancer cells. Second, the meso-chloro group of fluorophore A was not used to form conjugate 1.T he role of the meso-chloro functionality in the tumor-seeking properties of these dyes remainst ob ef ully elucidated, but we [21] and others [22] have shown that it is displaced by S-nucleophiles under physiological conditions, including the free cysteine residue in serum albumin.W eh ave also shown that the mesochloridec an be displaced to form ac ovalent albumin adduct that permeates into cancer cells.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[17] Conjugate 1 was designed to conform to several criteria. Second, the meso-chloro group of fluorophore A was not used to form conjugate 1.T he role of the meso-chloro functionality in the tumor-seeking properties of these dyes remainst ob ef ully elucidated, but we [21] and others [22] have shown that it is displaced by S-nucleophiles under physiological conditions, including the free cysteine residue in serum albumin.W eh ave also shown that the mesochloridec an be displaced to form ac ovalent albumin adduct that permeates into cancer cells. Second, the meso-chloro group of fluorophore A was not used to form conjugate 1.T he role of the meso-chloro functionality in the tumor-seeking properties of these dyes remainst ob ef ully elucidated, but we [21] and others [22] have shown that it is displaced by S-nucleophiles under physiological conditions, including the free cysteine residue in serum albumin.W eh ave also shown that the mesochloridec an be displaced to form ac ovalent albumin adduct that permeates into cancer cells.…”
mentioning
confidence: 99%
“…First, complexes of dasatinib with kinases [18][19][20] showt he nucleoside-like heterocyclic fragment buried in the active side of the enzyme, with its hydroxyethylene group projected into the aqueous medium ( Figure 1and Figure S1);t his indicates that A could be connected to the hydroxyethylene group without impeding the binding. Second, the meso-chloro group of fluorophore A was not used to form conjugate 1.T he role of the meso-chloro functionality in the tumor-seeking properties of these dyes remainst ob ef ully elucidated, but we [21] and others [22] have shown that it is displaced by S-nucleophiles under physiological conditions, including the free cysteine residue in serum albumin.W eh ave also shown that the mesochloridec an be displaced to form ac ovalent albumin adduct that permeates into cancer cells. [21b] Fluorophore A was conjugated with dasatinib (das) as described in the Supporting Information (selection of the amine base in this procedure proved critical).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The probe MHI-148 ( Fig. 53, Probe 81) was used to label free Cys residues, such as vimentin and serum albumin [102]. Other Cy-7 dyes containing meso-Cl (Fig.…”
Section: Application Of Nir Fluorescence Probes To Other Fieldsmentioning
confidence: 99%